The youth of the Roman emperors Caracalla and Geta: some reflexions on politics, family and numismatic - Gonçalves, Ana Teresa Marques (Romanitas - Revista de Estudos Grecolatinos, 2020)
In the Latin textual documents, produced in the 3rd and 4th centuries AD, we have little information about the youth of the sons and heirs of the Roman Emperor Lucius Septimius Severus with Julia Domna, Caracalla and Geta. They only became of interest to the authors when they ascended the imperial command in A.D. 211, after the death of their father, in Brittany, when they were respectively 23 and 22 years old. However, in order to promote family unity and the continuity of the Septimia gens in power, several coins were minted with the image of the heirs who were still very young and beardless. In this article, we seek to analyze the political use of family cohesion as a matrix of Severian governance, from the emission of messages via textual and numismatic supports, in which we identify representations of the still young Caracalla and Geta.
Keywords: Caracalla; Geta; Family; Youth; Coins